Consent to Specimen Storage and Continuing Studies by Race and Ethnicity: A Large Dataset Analysis Using the 2011-2012 National Health and Nutrition Examination Survey - Andre Gabriel; Catherine Crawford Cohen; Carolyn Sun (The Scientific World Journal)
Purpose. To determine if significant differences exist in consent rates for biospecimen storage and continuing studies between non-Hispanic Whites and minority ethnic groups in the National Health and Nutrition Examination Survey (NHANES). Methods. Using logistic regression, we analyzed 2011-2012 NHANES data to determine whether race/ethnicity, age, gender, and education level influence consent to specimen storage or future testing. Results. Compared to non-Hispanic Whites, some minorities were less willing to donate a specimen for storage and continuing studies, including other Hispanics (non-Mexican) (OR 0.236, 95% CI: 0.079, 0.706), non-Hispanic Asians (OR 0.212, 95% CI: 0.074, 0.602), and other/multiracial ethnic groups (OR 0.189, 95% CI: 0.037, 0.957). Within race and ethnic groups, those aged 20–39 years (OR 2.215, 95% CI: 1.006–4.879) and 40–59 years (OR 9.375, 95% CI: 2.163–40.637) are more willing than those over 60 years to provide consent. Conclusion. Lower consent rates by other Hispanics, non-Hispanic Asians, and other/multiracial individuals in this study represent the first published comparison of consent rates among these groups to our knowledge. To best meet the health care needs of this segment of the population and to aid in designing future genetic studies, reassessment of ethnic minority groups concerning these issues is important.